The Relationship Between Fast Food Consumption and the Incidence of Hypertension in Adults - Fasya Melivia, Jeanita; Everentia Ngasu, Kristina; Nur Puspita Sari, Dewi (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
People's habit of consuming fast food can have a negative impact on their health. there can be an increase in salt or sodium intake because fast food contains high levels of salt or sodium so that it can cause the risk of hypertension or increased high blood pressure. Objective to identify the relationship between fast food consumption (fast food) and the incidence of hypertension in adults. Research Design: quantitative research with a descriptive correlational design with a cross sectional approach. Sample Technique: non-probability sampling technique with purposive sampling method: 174 respondents. Data Analysis: Normality Test, Univariate Analysis, Bivariate Analysis. Results: analysis of the results with the chi-square test obtained a P-Value of 0.003 (<0.5). Conclusion: Based on the results of the study, it can be concluded that the consumption of fast food (fastfood) with the incidence of hypertension shows that there is a relationship between fast food consumption (fastfood) with the incidence of hypertension in adults.